Positioning the self and others linguistic perspectives - Beeching, Kate; Ghezzi, Chiara; Molinelli, Piera (Pragmatics & beyond., 2018)
"Though positioning has been addressed in social psychology and in identity construction, less attention has been paid to the specific linguistic markers which are drawn upon in discourse to position the self and other(s). This volume focuses on address terms, pragmatic markers, code switching/choice and orthography, the indexicalities of which are explored in different communicative activities. The volume is unusual in: i) the range of languages which are covered: Bergamasco, Brazilian Portuguese, English, Finnish, French, Georgian, Greek, Italian, Latin, Russian, Spanish and Swedish; ii) the inclusion of different communicative settings and text-types: workplace emails, everyday and institutional conversations, interviews, migrant narratives, radio phone-ins, dyadic and group settings, road-signs, service encounters; iii) its consideration of both synchronic and diachronic factors; iv) its mix of theoretical and methodological approaches. The volume illustrates some of the linguistic means speakers draw on to position themselves and others and hopes to stimulate further research studies in this vein"--